The Art of Laziness : overcome procrastination & improve your productivity - Library Mindset (India Notion Press, 2023)
Your time is very limited. An average person may get 80 summers in their entire life if they're lucky. A good amount of your life has already passed. When you put the time in this way, it doesn't appear too much. And yet you keep procrastinating, wasting time on things that don't matter to you. Is this how you want to live your entire life, or do you want to take charge of your life? You still have time; now let's put an end to this and finally start living.
English
Keywords: Health, Family & Personal Development